circ0093740 Promotes Tumor Growth and Metastasis by Sponging miR-136/145 and Upregulating DNMT3A in Wilms Tumor - Cao, Juan; Huang, Zhongying; Ou, Shunling; Wen, Feiqiu; Yang, Guocheng; Miao, Qiuling; Zhang, Huang; Wang, Yue; He, Xiaoxiao; Shan, Yingying; Liu, Sixi; Jiang, Lijuan (Frontiers in Oncology, 2021)
As a research hotspot, circular RNAs (circRNAs) is one type of non-coding RNAs (ncRNAs) which have many different functions in biological processes. However, there is lack of study investigating the underlying molecular mechanism and the potential roles of circRNAs in Wilms tumor. In this study, we conducted a high-throughput microarray sequencing to screen differentially expressed circRNAs in Wilms tumor. A novel circRNA (circ0093740) was identified as a frequently upregulated circRNA in Wilms tumor cells and tissues. Suppression of circ0093740 remarkably inhibited the proliferation and migration ability in Wilms tumor, validated by both in vitro and in vivo experiments. The molecular mechanism of circ0093740 was investigated by luciferase assays and RNA immunoprecipitation assays. The results revealed that circ0093740 promotes the growth and migration ability by sponging miR-136/145 and upregulating DNMT3A expression. In conclusion, our study discovered the biological role of the circ0093740-miR-136/145-DNMT3A axis in Wilms tumor growth and metastasis which is important for developing new treatment strategy.